Onomatopoeia in the Digital Manga Naruto: Shinden – Yukemuri Ninpouchou Chapters 1–15 - Aulia Rahmi; Nova Yulia (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2026)
Onomatopoeia refers to words that imitate or describe sounds, conditions, movements, or certain feelings. Its use is not limited to spoken communication but is also widely found in literary works such as novels and manga to strengthen visual impressions and enrich narrative expression. However, understanding onomatopoeia often poses challenges for learners or non-native speakers of Japanese due to its contextual nature and strong cultural specificity. This study aims to identify and describe the types and meanings of onomatopoeia found in the digital manga Naruto: Konoha Shinden – Yukemuri Ninpouchou Chapters 1–15. The data analysis is based on the classification theory of onomatopoeia proposed by Kindaichi and Asano (1978), as cited in Hinata and Hibiya, as well as Akimoto’s theory of onomatopoeic meaning (in Nihongo Kyouiku ni Okeru Onomatope no Kenkyuu, p. 30), referenced by Hasna and Hermansyah (2019). This research employs a qualitative approach using a descriptive method. Data were collected through documentation study of the manga, with the data consisting of all onomatopoeic expressions appearing in the text. The results reveal five types of onomatopoeia within a total of 54 data entries. The most dominant type is giyougo with 21 occurrences, while gijougo is the least frequent, appearing only once. Furthermore, eight out of ten categories of onomatopoeic meaning proposed by Akimoto were identified, including: imitation of natural phenomena (1 data), animal sounds (1 data), human sounds (10 data), human behavior (17 data), human states or feelings (5 data), object sounds (18 data), and object movements (1 data)